Silencing of OIP5-AS1 Protects Endothelial Cells From ox-LDL-Triggered Injury by Regulating KLF5 Expression via Sponging miR-135a-5p - Zhao, Minghu; Yang, Yuanyuan; Li, Jingchao; Lu, Min; Wu, Yu (Frontiers in Cardiovascular Medicine, 2021)
Background: Long non-coding RNAs (lncRNAs) have been implicated in the pathogenesis of atherosclerosis. LncRNA OIP5 antisense RNA 1 (OIP5-AS1) has been found to be associated with the development of atherosclerosis. In this study, we further investigated the molecular basis of OIP5-AS1 in atherosclerosis pathogenesis. Methods: Oxidative low-density lipoprotein (ox-LDL) was used to treat human umbilical vein endothelial cells (HUVECs). The levels of OIP5-AS1, miR-135a-5p, and Krüppel-like factor 5 (KLF5) were detected by quantitative real-time polymerase chain reaction (qRT-PCR) or western blot. Cell viability, migration, and apoptosis were evaluated using the Cell Counting Kit-8 (CCK-8), Transwell, and flow cytometry, respectively. The levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and malondialdehyde (MDA) were determined with enzyme-linked immunosorbent assay (ELISA). Targeted interactions among OIP5-AS1, miR-135a-5p, and KLF5 were confirmed by dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. Animal studies were performed to assess the role of OIP5-AS1 in atherosclerosis progression in vivo. Results: Our data showed the significant upregulation of OIP5-AS1 in atherosclerosis serum and ox-LDL-stimulated HUVECs. The silencing of OIP5-AS1 protected against ox-LDL-triggered cytotoxicity in HUVECs and diminished lipids secretion in ApoE−/− mice. Moreover, OIP5-AS1 functioned as a molecular sponge of miR-135a-5p, and miR-135a-5p was a functional mediator of OIP5-AS1 in regulating ox-LDL-induced HUVEC injury. KLF5 was a direct target of miR-135a-5p, and the increased expression of miR-135a-5p alleviated ox-LDL-induced cytotoxicity by downregulating KLF5. Furthermore, OIP5-AS1 influenced KLF5 expression through sponging miR-135a-5p. Conclusion: The current work identified that the silencing of OIP5-AS1 protected against ox-LDL-triggered cytotoxicity in HUVECs at least in part by influencing KLF5 expression via acting as a miR-135a-5p sponge.